Language Politeness on Social Networks among Upper Secondary Students: An Analysis of Politeness Principles (Jurnal Bahasa, 2022)
Linguistic politeness can be translated through the choice of a good word and the way it is spoken in a particular situation based on its purpose, such as greeting, asking, directing, or influencing. This study analyses language politeness on social media sites among upper secondary school students using Leech's (1983) Politeness Principle. The research instruments were derived from social media sites, such as Whatsapp and Facebook. The study also used qualitative methods, namely observation and questionnaires, to obtain data. During the field study, interviews and the distribution of questionnaires to respondents online were conducted to obtain the primary data. The study involved 60 male and female upper secondary school students from SMK Senawang and SMK Seri Pagi, located in Seremban, Negeri Sembilan, as respondents. The findings showed that in social media conversations, upper secondary school students most often showed a maximum use of politeness at 33.13%, a maximum use of agreement at 24.23% and a maximum use of humility at 42.64%. The strategic use of linguistic politeness in face-to-face and online conversations is based on the six maxims (maxim of politeness, maxim of kindness, maxim of support, maxim of agreement, maxim of humility and maxim of sympathy) found in Leech's Politeness Principle (1983). This Principle is found to help identify language politeness strategies in speakers who are upper secondary school students.Keywords: Politeness, Leech Politeness Principles, upper secondary, social sites, communication, maximFull text: PDF